Impact of collaterals on the efficacy and safety of endovascular treatment in acute ischaemic stroke: a systematic review and meta-analysis. Issue 5 (10th June 2015) - Leng, Xinyi; Fang, Hui; Leung, Thomas W H; Mao, Chen; Miao, Zhongrong; Liu, Liping; Wong, Ka Sing; Liebeskind, David S
Abstract : Objective: We aimed to investigate the role of pretreatment collateral status in predicting the efficacy and safety of endovascular treatment (EVT) in acute ischaemic stroke due to cervical and/or cerebral arterial occlusions. Methods: Relevant full-text articles published since 1 January 2000, investigating correlations between collateral status and any efficacy or safety outcome in patients undergoing EVT in cohort or case–control studies, or randomised clinical trials, were retrieved by PubMed and manual search. Two authors extracted data from eligible studies and assessed study quality. Risk ratios (RR) were pooled for good versus poor collaterals for outcomes based on a random-effects model. Sensitivity and subgroup analyses were conducted. Results: In total, 35 (3542 participants) and 23 (2652 participants) studies were included in qualitative review and quantitative meta-analysis, respectively. Overall, good pretreatment collaterals increased the rate of favourable functional outcome at 3 months (RR=1.98, 95% CI 1.64 to 2.38; p<0.001), and reduced the risks of periprocedural symptomatic intracranial haemorrhage (RR=0.59, 95% CI 0.43 to 0.81; p=0.001) and 3-month mortality (RR=0.49, 95% CI 0.38 to 0.63; p<0.001), as compared with poor collaterals, in patients with acute ischaemic stroke under EVT. No individual study could alter the estimate of overall effect of collateral status, but there were moderate to significant heterogeneities between subgroups of studies with different modes of EVT, different arterial occlusions and different collateral grading methods. Conclusions: Good pretreatment collateral status is associated with higher rates of favourable functional outcome, and lower rates of symptomatic intracranial haemorrhage and mortality, in patients with acute ischaemic stroke receiving endovascular therapies.